PENGEMBANGAN WEBSITE COMPETENCY TRAINING & SUPERVISION SERVICES MENGGUNAKAN METODE WATERFALL UNTUK GURU - Cipto, Yafie Arbian; Supriyanto, Achmad; Sunarni, Sunarni (Jurnal Visi Ilmu Pendidikan, 2025)
The development of science and technology is currently very rapid, especially in the field of education management. Teachers are required to master all competencies in order to be able to design and implement learning in accordance with existing regulations. The aim of this research is to create media that is easily accessible to teachers and easy to implement, to help teachers improve pedagogical and digital competence. The research uses the waterfall method in development which consists of five main stages, namely the first is analyzing user needs to find out the features needed on the website. Second is designing the website according to the needs analysis that has been determined using wireframes. The third is the development step using website programming languages such as PHP and HTML. The four testing steps are carried out by media experts, supervision experts and a supervisor, then there is a product feasibility test called a usability test using system usability scale (SUS) calculations. The final stage is maintenance, which functions to revise the product. The results of the development that have been tested by experts get a percentage value of 96% valid which can be used for expert 1, a value of 94% valid which can be used for expert 2, and a value of 92% valid which can be used for expert 3. Furthermore, the results of the usability test test get a value 95.4% which means that a product has an EXCELLENT value category, which means it can be used without any revisions and is very suitable for general use.